Loneliness and depression levels as risk factors of pain in geriatric prostate cancer patients - CICI, Remziye; YILMAZEL, Gulay; AYAZ, Nur Pınar (Universa Medicina, 2023)
BackgroundProstate cancer is the most prevalent malignancy among men, and psychological symptoms may affect many patients. Although much work has been carried out on loneliness, depression, and pain in geriatric prostate cancer patients, far less research has examined their associations. Therefore, the present study explored the association of loneliness and depression with pain in geriatric prostate cancer patients. MethodsA cross-sectional study was conducted involving 83 patients between the ages of 60 and 74 years, who were diagnosed with prostate cancer and were close relatives of students studying at a health sciences university. Data were collected with the Loneliness Scale for the Elderly, Beck Depression Inventory, and Numerical Rating Scale. The duration of prostate diagnosis was evaluated according to patient files. Simple and multiple logistic regression analyses were used to analyze the data. Results It was determined that the median age of the individuals included in the study was 66 years, and the median pain duration of these patients was two years. Severe pain was found in 62.7%, loneliness in 61.4%, and depression in 68.7% of the patients. Duration of diagnosis, loneliness, and depression were significantly associated with pain intensity. Depression increases the risk of pain intensity 3.41 times among patients (aOR=3.41;95% C.I.: 3.07-8.16; p=0.038) ConclusionIt was determined that duration of diagnosis, loneliness, and depression levels were risk factors for pain intensity in geriatric prostate cancer patients. Developing interventions for patients' mental states in rehabilitation studies may help alleviate the severity of pain.